Electrical Properties of Lead Borate Glasses Containing Different Alkali Metal Oxides - Salama, A.H.; Hammad, F.F. (Asian Journal of Chemistry, 2010)
The dc-electrical conductivity of lead borate glasses with different leadboron ratios and lead borate glasses containing basic cations of Na+, K+ and Mg2+ were measured in the temperature range (308-789 K). The activation energy of electrical conduction was calculated. It was found that all samples have semiconducting properties and fit well with the Arrhenius equation. The ac-electrical conductivities for these samples were calculated from the dielectric loss data to give a comparison between the ac- and dc-conductivity of borate glasses taking into consideration the effect of polarization of the molecule at high frequency. Differential thermal analysis was carried out for two samples to identify phase transition, which occurs in the used temperature range. All results are discussed and correlated to the molecular structure of the prepared glasses.